Modifying urban planning to promote child health: A scoping review of reviews - Louise Wallerich; Jean Simos; Linda Cambon (Health Promotion Perspectives)
Background: Children’s health is shaped by their physical, natural, and socioeconomic environments. The objective of this study is to identify structural urban planning measures that can positively or negatively impact children’s health. Specifically, we aim to explore how urban planning elements, such as housing, neighborhoods, play areas, and green spaces, influence children’s well-being and health outcomes. Methods: We conducted a scoping review in accordance with the method developed by Arksey and O’Malley, Levac and colleagues’ methodology advancement, and the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guideline. We explored eight databases, restricting our search to reviews, systematic reviews, and meta-analyses that report on structural measures aimed at modifying urban planning to promote child health. Results: A total of 41 studies were identified for inclusion in this review. The thematic analysis identified: i) interventions aimed at modifying streets; ii) interventions aimed at modifying play areas; iii) interventions aimed at modifying contact with nature; iv) interventions aimed at modifying deleterious exposures (exposure to tobacco, exposure to school); and v) housing. The second level of analysis enabled us to identify and evaluate the conditions for implementation and effectiveness. Conclusion: The review highlighted measures that are favorable to children’s health at the level of neighborhood urban planning and questioned the conditions for implementation in a French context.